2004
DOI: 10.1523/jneurosci.4839-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Perirhinal Cortex Supports Delay Fear Conditioning to Rat Ultrasonic Social Signals

Abstract: Auditory information can reach the lateral nucleus of the amygdala (LA) through a monosynaptic thalamic projection or a polysynaptic cortical route. The polymodal input from the perirhinal cortex (PR) is a major informational gateway to the LA and nearby structures. Pretraining PR lesions impair fear conditioning to a context, but there have been no reports that they cause deficits in delay conditioning to an auditory cue. The direct subcortical projection to the LA seems sufficient to support delay conditioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 61 publications
7
89
1
Order By: Relevance
“…The selection of PR as an initial region of interest was partly based on the discovery that damage to this structure impairs fear conditioning to USVs [24,29] but has no significant effect on conditioning to continuous tones [10,24,29,34]. The fact that cortical processing is not necessary for conditioning to continuous tones is commonly interpreted to mean that activity in the subcortical projection from the auditory thalamus to the amygdala is sufficient to represent these relatively simple stimuli [22,34,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The selection of PR as an initial region of interest was partly based on the discovery that damage to this structure impairs fear conditioning to USVs [24,29] but has no significant effect on conditioning to continuous tones [10,24,29,34]. The fact that cortical processing is not necessary for conditioning to continuous tones is commonly interpreted to mean that activity in the subcortical projection from the auditory thalamus to the amygdala is sufficient to represent these relatively simple stimuli [22,34,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Similar auditory stimuli have previously been used as cues to support Pavlovian fear conditioning [24]. Experiment 2 used 6 stimuli (including 4 new ones) that were designed to isolate certain features of USVs that may be responsible for eliciting single-unit responses: 2 pre-recorded USVs (~65 dB SPL), which differed markedly from each other in terms of call structure; 2 frequency-and temporally-matched tone segments (10 ms rise/fall time, 65 dB SPL); and 2 frequency-matched continuous tones (10 ms rise/fall time, 65 dB SPL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a multitude of recent studies have shown that discontinuous tones (including ultrasonic vocalisations) recruit the perirhinal cortex but continuous tones do not (Kholodar-Smith et al, 2008a;Bang and Brown, 2009b). Confirmation of these findings come from electrophysiological data which shows that there are different firing patterns observed in the perirhinal cortex during exposure to discontinuous tones compared to continuous tones (Furtak et al, 2007c) and from lesions of the perirhinal cortex where there is impairment of conditioning to ultrasonic vocalisations but not to continuous tones (Lindquist et al, 2004). These results fit with the data generated from recognition and fear conditioning tasks where the perirhinal cortex is required for processing more complex stimuli and contexts (Corodimas and LeDoux, 1995;Sacchetti et al, 1999;Bucci et al, 2000Bucci et al, , 2002Bussey et al, 2000;Eacott et al, 2001;Burwell et al, 2004a).…”
Section: The Role Of the Perirhinal Cortex In Fear Conditioningmentioning
confidence: 92%